Strategiczne planowanie kadrowe - Penc-Pietrzak, Ilona (Wydawnictwo Media Press, 2008)
Modem management requires the skill of strategie planning, especially human resources planning. It is so important because human resources are a very precious capital of organization. The article presents characteristics, tasks and stages of this planning, irregularities and mistakes made by planners and rules of effective human resources planning.
Keywords: planowanie kadrowe; strategiczne planowanie kadrowe; zarządzanie zasobami ludzkimi; błędy w planowaniu kadrowym; efektywne planowanie kadrowe; human resources planning; strategic personnel planning; human resource management; mistakes in personnel planning; effective human resource planning